Trends and Challenges in Anomaly Intrusion Detection at the Edge for IoT: A Review - Amrullah, Ata; Kardono, Dicka Yale; Abidin, Mohammad Mansyur (Intellithings Journal, 2025)
The rapid proliferation of Internet of Things (IoT) devices has brought about new security challenges, particularly in the area of intrusion detection. This review article provides a comprehensive analysis of the trends and challenges in anomaly intrusion detection at the edge for IoT. By synthesizing findings from recent literature (2021-2023), we explore various approaches to anomaly detection, including those based on machine learning (ML), deep learning (DL), statistical methods, and rule-based techniques. We also examine network attacks relevant to IoT, such as man-in-the-middle (MitM), replay, and injection attacks. Our findings reveal a growing trend towards the use of ML and DL for anomaly detection, with many studies focusing on hybrid approaches to improve detection accuracy. While edge computing offers advantages in terms of reduced latency and enhanced privacy, significant challenges remain in implementing anomaly detection on resource-constrained edge devices. These include the heterogeneity of devices and protocols, the increasing sophistication of cyberattacks, the limited availability of labeled data, and privacy concerns. This review identifies unresolved research gaps, including the need for more efficient algorithms, more adaptive approaches, methods for generating synthetic anomaly data, and large-scale implementations. Furthermore, this work discusses the practical implications for enhancing IoT security and provides guidance for researchers and practitioners in the field. We conclude that future efforts should emphasize the development of adaptive and efficient methods, particularly for real-time detection, and consider ethical aspects like data privacy in the deployment of anomaly detection at the edge.